PENGARUH KESADARAN, SAMSAT DRIVE THRU, E-SAMSAT, DAN SISTEM PEMUTIHAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI SAMSAT KOTA DENPASAR - Putri, Tiara Hanifah Budika; Jati, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 12 No 6 (2023): Vol.12.6.JUNI.2023[376-450]DO - 10.24843/EEP.2023.v12.i06.p01, 2023)
This study analyzes the impact of taxpayer awareness, Samsat drive-thru services, e-Samsat, and the tax write-off program on the level of motor vehicle taxpayer compliance. This is done due to the decreasing public awareness of fulfilling tax obligations, which is not in line with the increase in the number of vehicles each year. This research was conducted to analyze the effect of taxpayer awareness, Samsat drive-thru services, e-Samsat, and the tax write-pff program on public awareness in terms of fulfilling vehicle tax obligations. The sample in this study amounted to 100 motor vehicle taxpayers. The use of a questionnaire is a method used to collect the required data. The data analysis technique used is Multiple Linear Analysis. The results showed that the four hypotheses proposed were acceptable, which means that taxpayer awareness, Samsat drive-thru services, e-Samsat, and tax write-off program have a significant influence on the level of public awareness of fulfilling motor vehicle tax obligations. Keyword : Taxpayer Awareness, Drive Thru Samsat, E-samsat, Pemutihan Pajak, Taxpayer Compliance.